Cancer in patients receiving dialysis. - Kinlen, L; Eastwood, J; Kerr, D; Moorhead, J; Oliver, DO; Robinson, B; de Wardener, H; Wing, A (1980)
The incidence of cancer and related mortality was studied in 1651 patients from six dialysis centres in England over 10 years. The only type of cancer for which there was a significant excess was non-Hodgkin's lymphoma (four cases observed against an expected incidence of 0.15 (p < 0.001); three deaths against an expected 0.1 (p < 0.001)). This excess could not be attributed to either subsequent transplantation or treatment with immunosuppressive drugs. Since immunodepression is a feature of chronic renal failure, these observations together with those on patints treated with immunosuppressive drugs suggest that immunosuppression favours the development of non-Hodgkin's lymphoma. Studies in which it is concluded that patients receiving dialysis show an excess of other types of cancer have certain shortcomings; the unusual opportunities for detecting cancer in such patients may account for some of the reported excess.